Identyfikacja kosztów outsourcingu w rachunkowości - Nadolna, Bożena (The Identification of Outsourcing Costs in Accounting, 2006)
Outsourcing is a long term, results-oriented relationship in which the non-profit business processes are transferred to an external service provider. Accounting is an area in which outsourcing makes the most sense because accounting is rarely a core competency within company. The aim of the paper is the identification of outsourcing cost in accounting and to present the benefits from the outsourcing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 284-294